Inhibitory Activities of Thai Culinary Vegetables against Key Enzymes Relevant to Diabetes Mellitus and the Kinetics of Enzyme Inhibitions - Khakhanang Ratananikom; Panorjit Nitisuk; Panida Wongpreedee; Jittawan Kubola (Journal of Food Quality)
Diabetes mellitus (DM) is one of the most challenging noncommunicable diseases, as it causes significant costs for medical treatment as well as high morbidity and mortality rates. Dietary plants with antidiabetic properties have been explored as an alternative to synthetic medicines to treat DM because of their safety and nutrition. Hence, the objective of the present study was to determine the inhibitory activities of twenty commonly consumed Thai culinary vegetables against α-glucosidase and α-amylase. All vegetables were extracted using deionized water, ethanol, and hexane at 150 rpm and 30°C for 24 hours. The enzyme inhibitory activities were performed using a colorimetric assay. Diverse results for α-glucosidase and α-amylase inhibitory activities were found for all vegetable extracts. The most potent anti-α-glucosidase activity was obtained from the ethanolic extract of Leucaena leucocephala (Lamk.) de Wit with the half maximal inhibitory concentration (IC50) of 13.39 ± 0.14 μg/mL, followed by the aqueous and ethanolic extracts of Polygonum odoratum Lour with IC50 of 25.60 ± 0.42 and 49.03 ± 0.72 μg/mL, respectively. All the samples exhibited mixed, noncompetitive, and uncompetitive inhibition. It can be concluded that the α-glucosidase and α-amylose inhibitory effects of the investigated extracts may be an indicator of antidiabetic potency, and these extracts might potentially be beneficial as functional components for postprandial hyperglycemia treatment.